2018
DOI: 10.1111/cars.12180
|View full text |Cite
|
Sign up to set email alerts
|

Islamophobia in Canada: Measuring the Realities of Negative Attitudes Toward Muslims and Religious Discrimination

Abstract: There has been growing discussion surrounding the phenomenon of Islamophobia in Western societies over the last few years. However, in-depth empirical research of the prevalence and patterns of prejudice toward Muslims remains scarce, especially in the Canadian context. With data from the 2011 Canadian Election Study and the 2014 General Social Survey, this study measures the extent to which negative feelings toward Muslims are present among the general adult population, and the extent to which Muslim Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 39 publications
(43 reference statements)
1
43
0
5
Order By: Relevance
“…On one hand, welcoming refugees can be understood as a performance of Canadian friendliness or the Canadian commitment to humanitarian action. However, most refugees belong to racialized communities, particularly Muslim, Arab and African, which are subject to prejudice and discrimination throughout Canadian society (see, for example, Wilkins-Laflamme, 2018). It is possible—even likely—that refugees are “valuable” immigrants in that they are refugees, but are “devalued” through their racialization, and that this fluid relationship to value in the perspectives of (largely white) Canadian sponsors can affect which acculturation attitudes they demonstrate.…”
Section: Canadian Attitudes Towards Immigrationmentioning
confidence: 99%
“…On one hand, welcoming refugees can be understood as a performance of Canadian friendliness or the Canadian commitment to humanitarian action. However, most refugees belong to racialized communities, particularly Muslim, Arab and African, which are subject to prejudice and discrimination throughout Canadian society (see, for example, Wilkins-Laflamme, 2018). It is possible—even likely—that refugees are “valuable” immigrants in that they are refugees, but are “devalued” through their racialization, and that this fluid relationship to value in the perspectives of (largely white) Canadian sponsors can affect which acculturation attitudes they demonstrate.…”
Section: Canadian Attitudes Towards Immigrationmentioning
confidence: 99%
“…It is important to note, however, that despite Canadian Muslims’ tendency toward adopting the Canadian way of life, Canadians have more negative feelings toward Muslims than other groups (Fournier et al. ; Wilkins‐Laflamme ).…”
Section: Acculturation Strategiesmentioning
confidence: 99%
“…although Islam is the fastest growing religion among Canada's immigrant population (see Statistics Canada 2011). It is important to note, however, that despite Canadian Muslims' tendency toward adopting the Canadian way of life, Canadians have more negative feelings toward Muslims than other groups (Fournier et al 2015;Wilkins-Laflamme 2018).…”
Section: Integraɵon Marginalizaɵon Assimilaɵon Separaɵonmentioning
confidence: 99%
“…Indeed, in the context of Islamophobia there has been an increase in anti-Islamic or Muslim hate-related incidents in the U.S. over the past 20 years (see Figure 1; Federal Bureau of Investigation, 2000-2017). Studies including Muslims in the U.S., Canada, and Europe have consistently found high rates of Running head: PREDICTORS OF MENTAL HEALTH FOR MUSLIMS perceived discrimination directed to the self or towards people they know (Ashraf & Nassar, 2018;Sirin & Fine, 2007;Nadal et al, 2012;Brüß, 2008;Wilkins-Laflamme, 2018). Qualitative research has also found Muslims report unique experiences of discrimination compared to other marginalized, minority groups in the United States (Nadal et al, 2012;Sirin & Fine, 2007) and Europe (e.g., Moffit et al, 2018).…”
Section: Racialization Islamophobia and Discriminationmentioning
confidence: 99%